Sensing technology : current status and future trends III - Mason, Alex (Springer, 2015)
This book contains a collection of selected works stemming from the 2013 International Conference on Sensing Technology (ICST), which was held in Wellington, New Zealand. The purpose of the book is to distill the highlights of the conference, and therefore track the latest developments in sensing technologies. The book contents are broad, since sensors can be applied in many different areas. Therefore the book gives a broad overview of the latest developments, in addition to discussing the process through which researchers go through in order to develop sensors, or related systems, which will become more widespread in the future. The book is written for academic and industry professionals working in the field of sensing, instrumentation and related fields, and is positioned to give a snapshot of the current state of the art in sensing technology, particularly from the applied perspective.